Design and implementation home security system and monitoring by using wireless sensor networks WSN/internet of things IOT - H. H. Qasim; A. E. Hamza; H. H. Ibrahim; H. A. Saeed; M. I. Hamzah (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The dramatic advancments on communication and networking technologies have led to the emergence of Internet-of-Things (IoT). IoT technology has opened the door for various applications. In particular, the home automation was one of the common applications that took the advantage of IoT. Several research efforts have addressed the home automation system using IoT covering wide range of functionalities. One of the concerning tasks is providing a secure system that can give alarms for suspicious activities within the house. This paper presents a secure house system based on IoT where several activities are being sensed and detected. Specifically, gas, humidity, body temperature and motion have been considered within the sensing based on two main types of micro-controller including Arduino and Raspberry Pi. Consequentially, an Android prototype has bene developed in order to give an interactive interface for warning the house owner regarding any suscpicious activities. Results of simulation demonstrated the efficancy of the proposed system